Berjelajah dalam Sensasi: Wisata Virtual Sebagai Hiburan Praktis Pemuda Urban - Hasbullah, Abdul Wahab; Sujibto, B.J. (Jurnal Studi Pemuda, 2024)
COVID-19 pandemic has contributed to the emergence of various innovations and developments in the social lives, especially in accelerating the utilization of the virtual world. One of the innovations offered is virtual tourism, which has begun to be popular among young people. Virtual tourism is utilized by urban communities, especially young people, as a new alternative in tourism practices involving technology and social media. This article discusses virtual tourism, which is widely practiced by urban youth in Yogyakarta. Various factors, motivations, and experiences of young people in virtual tourism are the topics investigated in this article. By using a qualitative method through observation and in-depth interviews with seven informants practicing virtual tourism, this article found several interesting points: (1) virtual tourism has become a practical alternative holidaychoice for urban youth, (2) the advancements and conveniences offered by social media as tools for virtual tourism, and (3) the livelier expression of young people’s imagination in virtual tourism of both natural and urban landscapes. Driving factors such as digital technology facilities are determinants for virtual tourism practices that can contribute to digital humanities.